Expression Stabilities of Candidate Reference Genes for RT-qPCR in Chinese Jujube (Ziziphus jujuba Mill.) under a Variety of Conditions - Bu, Jiaodi (PLoS One, 2016)
Reverse transcription-quantitative real-time polymerase chain reaction (RT-qPCR) is a powerful method for evaluating patterns of gene expression. Jujube whole-genome sequencing has been completed, and analysis of gene function, an important part of any follow-up study, requires the appropriate selection of reference genes. Indeed, suitable reference gene selection for RT-qPCR is critical for accurate normalization of target gene expression. In this study, the software packages geNorm and NormFinder were employed to examine the expression stabilities of nine candidate reference genes under a variety of conditions. Actin-depolymerizing factor 1 (ACT1), Histone-H3 (His3), and Polyadenylate-binding protein-interacting protein (PAIP) were determined to be the most stably expressed genes during five stages of fruit development and ACT1, SiR-Fd, BTF3, and Tubulin alpha chain (TUA) across different tissues/organs. Whereas ACT1, Basic Transcription factor 3 (BTF3), Glyceraldehyde-3-phosphate dehydrogenase (GADPH), and PAIP were the most stable under dark conditions. ACT1, PAIP, BTF3, and Elongation factor 1- gamma (EF1γ) were the most stably expressed genes under phytoplasma infection. Among these genes, SiR-Fd and PAIP are here first reported as stable reference genes. When normalized using these most stable reference genes, the expression patterns of four target genes were found to be in accordance with physiological data, indicating that the reference genes selected in our study are suitable for use in such analyses. This study provides appropriate reference genes and corresponding primers for further RT-qPCR studies in Chinese jujube and emphasizes the importance of validating reference genes for gene expression analysis under variable experimental conditions.